KHONZODA BEGIM – A POLITICALLY ACTIVE WOMAN OF THE TEMURID PERIOD - Begimqulova L. M; Yigitaliyeva Sh. Sh. (TARIXIY TADQIQOTLAR, 2025)
This article extensively covers the life, political activities and historical legacy of one of the prominent female representatives of the Timurid dynasty - Sevin Begum Khanzoda (Khonzoda Begim). Her role in strengthening diplomatic relations between the Timurids and Genghis, as well as her position in the Timurid court, is analyzed based on scientific sources. The article covers the issues of Khanzoda Begim's personal life, political activities, participation in the cultural life of the court and the role of medieval women in state administration. is covered based on historical sources.